Do Changes in Sovereign Credit Ratings Contribute to Financial Contagion in Emerging Market Crises? - Roman Kraeussl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
Credit rating changes for long-term foreign currency debt may act as a wake-up call with up-grades and downgrades in one country affecting other financial markets within and across national borders. Such a potential (contagious) rating effect is likely to be stronger in emerg-ing market economies, where institutional investors' problems of asymmetric information are more present. This empirical study complements earlier research by explicitly examining cross-security and cross-country contagious rating effects of credit rating agencies' sovereign risk assessments. In particular, the specific impact of sovereign rating changes during the fi-nancial turmoil in emerging markets in the latter half of the 1990s has been examined. The results indicate that sovereign rating changes in a ground-zero country have a (statistically) significant impact on the financial markets of other emerging market economies although the spillover effects tend to be regional.
urn:nbn:de:hebis:30-10271
Keywords: E44; E47; G15; 330; Sovereign Risk; Credit Ratings; Financial Contagion